Modification of Flood Vulnerability Models Based on BNPB Regulation 2012 (Case Study: Jatiroto Watershed, Lumajang) - Athallah, Regina Salsabila; Suharyanto, Agus; Wijatmiko, Indradi (Rekayasa Sipil, 2026)
Floods are the most frequent natural disaster in Indonesia and have caused significant social, economic, and environmental losses, making mitigation measures based on regional vulnerability essential. Flood risk assessments in Indonesia generally rely on InaRISK maps developed by the National Disaster Management Agency (BNPB). This study develops a modified flood vulnerability calculation model based on BNPB Regulation No. 2 of 2012. It compares its results with the InaRISK vulnerability map for the Jatiroto watershed in Lumajang Regency. The analysis considers four components: social, economic, infrastructure, and ecology, with the main novelty being the reversal of ecological weighting so that larger areas of forests, shrubs, and swamps reduce, rather than increase, vulnerability, in line with hydrological reasoning. The modified model yields an RMSE of 0.224 and an MAE of 0.203, with an NRMSE of 0.23 and an NMAE of 0.21, indicating good agreement with InaRISK (NRMSE < 0.3). The findings show that adjusting ecological parameters can produce a more contextual and accurate vulnerability pattern and provide a simple, public-data-based alternative for local governments to update flood vulnerability maps and potentially inform future refinement of ecological parameters in national flood risk guidelines.